Design and Development of a Hydrogen Sulfide Early Detection Device in The Human Mouth - Handayani, Arivia Fitra; Wijaya, Nur Hudha; Untara, Bambang; Kartika, Wisnu (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Health serves as a reference for mental, physical, and social well-being. Dental and oral health are vital in human life. Minister of Health Regulation No. 89 of 2015 concerning dental and oral health emphasizes the importance of healthy states of hard and soft tissues and elements related to the oral cavity. Oral diseases include both acute and chronic health problems that attack the oral system. Hydrogen sulfide (H2S), a gas widely produced in the oral cavity, is the main cause of oral diseases. Microorganisms in the oral cavity are the producers of volatile sulfur compounds (VSC) caused by food waste. Three main amino acids make up VSC: cysteine, which produces hydrogen sulfide (H2S); methionine, which yields methyl mercaptan (CH3SH); and cystine, which generates dimethyl sulfide (CH3SCH3). This research designed a hydrogen sulfide early detection device in the human mouth. This proposed module worked by relying on the principle of detecting the density of hydrogen sulfide gas in the oral cavity using the TGS2602 gas sensor. The test of this proposed module device involved two respondents. The test was conducted in the morning, afternoon, and evening for three consecutive days. The results revealed that the average value of the first respondent was 0.25 PPM on day 1, 0.29 PPM on day 2, and 0.20 PPM on day 3. Meanwhile, the second respondent obtained 0.28 PPM on day 1, 0.29 PPM on day 2, and 0.27 PPM on day 3.